HARDWARE IN THE LOOP TESTING OF A PROTECTION MONITORING AND DIAGNOSTIC SYSTEM - Černelič, Jernej; Polajžer, Boštjan; Zakonjšek, Janez; Nebera, Alexey; Hrovat, Gorazd (Journal of Energy Technology, 2025)
Protection, automation, and control (PAC) devices are very important for the reliable operation of electric power systems (EPS), which can be improved further by monitoring the PAC devices. One way is to apply a protection monitoring and diagnostic (PMD) system, which was tested using a real-time digital simulator and two numerical protection relays in the hardware in the loop configuration. Furthermore, the communication between the protection relays and the PMD system was also tested, while the EPS faults were simulated in a safe environment on a digital simulator in real-time. When a fault occurs in the EPS, the PMD system performs the fault analysis, and generates a disturbance report within several minutes after the fault. The tested PMD system also gathers all protection relays’ settings, thus reducing the workload of protection specialists significantly.